Проблеми ефективності законодавства України - Дубина, Н. А.; Dubina, N. A.; ORCID: http://orcid.org/0000-0003-4432-4309; Турута, О. В.; Turuta, O. V. (Право і безпека. - 2015. - № 2 (57). - С. 23-27., 2015)
Здійснено систематизацію поглядів стосовно причин виникнення юридичних колізій. Сформульовано негативні та позитивні аспекти їх існування. Визначено роль вказаного явища у національній правовій системі. Наведено перелік умов, необхідних для забезпечення ефективності законодавства. Проаналізовано вплив суспільної думки на правотворчий процес.

Studying the problems of the efficiency of Ukrainian legislation is very relevant taking into account the current stage of development of the society, which is characterized by its integration into European political, economic and legal space. All this requires adaptation of Ukrainian legislation to European Union law. The current amendments in the legislation are characterized by complexity, inconsistency, instability that lead to the growth and occurrence of conflicts not previously known. Under such conditions there is an urgent issue related to the reasons for the emergence of legal conflicts and their existence in the legislation of Ukraine. The points of view concerning legal conflicts are systematized in this paper; the causes of their origin are singled out; their place and role in the national legal system are defined. The list of conditions that are necessary to ensure the effectiveness of the legislation is provided. It is noted that there is no and there will not be legal systems, which would be inherent such a phenomenon as legal conflicts. They reflect changes in the legal system or in its individual elements, objective modernize of government institutions and act as evidence of the normal process of development and functioning of the legal system. It is concluded that the effectiveness of the national legal system depends on a complex of factors. It is stated that to the low efficiency of legal norm may lead: first, its discrepancy to existing system of social relations; secondly, a negative evaluation of legal norm by the society; thirdly, contradictions of the newly adopted legal norm with already active, and between procedural norms, which are endowed with different or the same legal force.

Систематизированы взгляды относительно причин возникновения юридических коллизий. Сформулированы негативные и позитивные аспекты их существования. Определена роль исследуемого явления в национальной правовой системе. Перечислены необходимые условия для повышения эффективности законодательства. Проанализировано влияние общественного мнения на правотворческий процесс.
Dubina, N.A. and Turuta, O.V. (2015), “Problems of the efficiency of Ukrainian legislation” [“Problemy efektyvnosti zakonodavstva Ukrainy”], Pravo i Bezpeka, No. 2, pp. 23–27.
Дубина, Н. А. Проблеми ефективності законодавства України / Н. А. Дубина, О. В. Турута // Право і безпека. - 2015. - № 2 (57). - С. 23-27.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; законодавство; юридичні колізії; правові норми; суспільство; legislation; legal conflicts; legal norms; reasons for conflicts; legal regulation; society; законодательство; юридические коллизии; правовые нормы